التحفيز الكهربائي (body relax) في علاج الالام المزمنة لأسفل الظهر للاعبي القوة البدنية المتقدمين - حسين, عصام طالب عباس; حمزة, حيدر عبد علي (Sulaimani Journal for Humanities, 2018)
Summary The authors of the study described not the cause of chronic low back pain of physical strength players. The importance of the study was to relieve pain in the lower back muscles and reduce the complications resulting from the reduction of chronic pain using a type of electrical stimulation with frequencies dedicated to the purpose of muscle relaxation The problem of research is not to use technical means in the rehabilitation of lower back injuries to the players of physical strength applicants The aim of the research was to use the EMS type body relax in the treatment of chronic low back pain and to know its effect on those with the pain The researcher hypothesized the electrical stimulation used by the researchers positively affect the reduction of chronic pain and rehabilitation of the muscles of the lower back of physical strength players under consideration The research method used the experimental method of one group and identified the research community with players suffering from low back pain in the physical strength of the successors in Najaf and the sample of the study (6) injured players were chosen deliberately, and used a form of measuring the degree of pain according to the test Shopper and physical tests The training program included the use of EMS for muscle relaxation and the researchers used the statistical program spss and used the following statistical means mediator, spring deviation, Man and Whitney The most important conclusions reached by the researchers 1- For the special electrical stimulation of the muscle relaxant body relax a significant role in reducing the level of chronic pain down the back and improve the physical flexibility of the muscles of the lower back of the players of physical strength applicants The most important recommendations recommended by the researchers are 1- the need to use modern technology in the treatment of chronic low back pain 2 - Benefit from the technology of electric stimulation EMS in the development of strength and flexibility of the muscles of the trunk to prevent the incidence of lower back injuries.